Penyuluhan Hukum Tentang Potensi Korupsi di Sektor Desa Bagi 330 Desa di Kabupaten Sumenep - Dewi Ambarwati; Dafis Assiddiq; Muhammad Imron (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2024)
Today's village is a subject of development that has legitimacy in managing its own government affairs that are tailored to the potential and characteristics of the village. In line with this, an understanding of the vision related to village development is needed to realize independent villages. However, the realization of independent villages still encounters several crucial obstacles, such as the quality of human resources, organizational management and utilization of natural resources that are still minimal to the existence of corruption in the village sector. For this reason, a legal counseling activity related to corruption education for village governments is needed. This service activity was carried out in Sumenep Regency involving 330 village heads. The method used in this service activity is to use the PAR (Participatory Action Research) method. The purpose of this activity is to provide understanding and as one aspect of strengthening the prevention of potential corruption in the village sector. This activity was carried out for 3 (three) days, which was carried out using the method of discussion and socialization about the types of corruption crimes and the potential for corruption in the village. The result of this activity is an increase in community participation together with village officials to suppress corruption through a